2020
DOI: 10.1002/nafm.10429
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study to Evaluate Biases in Population Characteristics Estimation Associated with Varying Bin Numbers in Size‐Based Age Subsampling

Abstract: In temperate waters, growth and mortality of bony fishes are frequently estimated from age information derived from the examination of annular rings on hard structures (e.g., otoliths). However, determining ages from hard structures can be time consuming, often requires sacrificing fish, and has associated costs for supplies and personnel time in processing or reading structures. Subsampling based on a target number of fish per length bin is commonly used to reduce time and costs but may introduce biases into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…For age‐classes in which the number of fish was fewer than 1,000 individuals, all data were used. Age‐based subsampling was recently demonstrated to be unbiased (Goodyear 2019), but neither that study nor the present study evaluated this assumption relative to gear selectivity, although this can be an important consideration (Hilling et al 2020). Therefore, we also ran models with subsamples of 10 and 100 fish per system per year to confirm that this choice did not arbitrarily influence model selection or statistical inference.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…For age‐classes in which the number of fish was fewer than 1,000 individuals, all data were used. Age‐based subsampling was recently demonstrated to be unbiased (Goodyear 2019), but neither that study nor the present study evaluated this assumption relative to gear selectivity, although this can be an important consideration (Hilling et al 2020). Therefore, we also ran models with subsamples of 10 and 100 fish per system per year to confirm that this choice did not arbitrarily influence model selection or statistical inference.…”
Section: Methodsmentioning
confidence: 83%
“…First, we assumed that the wide range of gears and methods used for fish collection were representative of these populations through time. Importantly, it has been demonstrated that gear selectivity can influence estimated VBGF parameters (Gwinn et al 2010) and in some instances can even override attempts to correct this through size-based subsampling within gears (Hilling et al 2020). Through inclusion of multiple gears and collection, our intention was to minimize the potential for bias from any given gear.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the aged subsample is not a random sample of either the entire sample or the population, as these data are collected according to a fixed number of individuals per length‐group. Using a length‐stratified aged subsample without incorporating information from the entire sample has the potential to drastically bias growth estimates and should not be used to directly evaluate growth (Chang et al 2019; Goodyear 2019; Hilling et al 2020; Perreault et al 2020). Evaluating growth with length‐stratified subsampled age data should employ a method to “expand” those data to the entire sample such that estimation uses information from all fish collected (i.e., account for the length‐stratified sampling design).…”
mentioning
confidence: 99%
“…The reweighting method of Chih (2009) estimates growth parameters by fitting the VBGM to length–age data in the aged subsample, where each observation is weighted by the ratio of the proportion of fish from the entire sample that belong to the fish’s length‐bin to the proportion of fish from the aged subsample that belong to the fish’s length‐bin. Hilling et al (2020) found that the reweighting method accurately estimated growth parameters for the population in some cases but performed poorly in other cases (e.g., with dome‐shaped selectivity when extracting the entire sample from the population). Perreault et al (2020), expanding on the work of Zhang and Cadigan (2019), described several methods for estimating growth that were based on the statistical theory of double sampling.…”
mentioning
confidence: 99%
See 1 more Smart Citation